2018
DOI: 10.1684/epd.2018.0963
|View full text |Cite
|
Sign up to set email alerts
|

Ictal spitting in non‐dominant temporal lobe epilepsy: an anatomo‐electrophysiological correlation

Abstract: We report a patient presenting drug‐resistant, non‐dominant temporal lobe epilepsy with ictal spitting and prosopometamorphopsia, both extremely rare semiologies. Second‐phase pre‐surgical monitoring was performed using SEEG due to lesion‐negative imaging and the rare semiology. The seizure onset zone was delimited to the right anterior hippocampus and the temporobasal cortex, with the propagation zone within the entorhinal cortex. Interestingly, direct electrical stimulation to the entorhinal cortex, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…Spitting is an infrequent symptom reported in 0.3-2% of patients with temporal lobe seizures [296,[307][308][309][310], and several studies implicate non-dominant lateralization [296,[310][311][312]. However, the left temporal lobe has also been involved in case reports [309,313,314].…”
Section: Spittingmentioning
confidence: 99%
See 1 more Smart Citation
“…Spitting is an infrequent symptom reported in 0.3-2% of patients with temporal lobe seizures [296,[307][308][309][310], and several studies implicate non-dominant lateralization [296,[310][311][312]. However, the left temporal lobe has also been involved in case reports [309,313,314].…”
Section: Spittingmentioning
confidence: 99%
“…In a case report evaluated with invasive EEG electrodes, although the seizure onset zone was in the left mesial temporal lobe, the ictal spitting coincided with the propagation of the ictal discharge to the right temporal lobe, implicating the latter as the symptomatogenic zone [312]. Direct electrical stimulation studies during invasive EEG monitoring have identified the entorhinal cortex as a site involved in ictal spitting [311]. Ictal spitting does not occur in association with ictal vomiting, ictal coughing, or ictal fear, suggesting there are different sites in the brain that mediate these symptoms with unique specificity [308].…”
Section: Spittingmentioning
confidence: 99%
“…Ictal swearing is more common among males, with lateralization to the non-dominant hemisphere. 2,4,6 However, Massot-Tarrús et al…”
Section: Discussionmentioning
confidence: 99%
“…Quevedo-Diaz ve ark. [10] ilaca dirençli, sağ temporal lob başlangıçlı, iktal tükürme ve prosopometamorfopsi ile başvuran bir hastayı iyi dökümente etmişler ve doğrudan elektriksel stimülasyon ile iktal tükürme oluşturmuşlardır. Ameliyat sonrası 5 yıl nöbetsiz izledikleri olgularında bazal temporal ve entorinal korteksin iktal tükürmede önemli rol oynadığını göstermişlerdir.…”
Section: Discussionunclassified
“…[3][4][5][6][7] Özellikle peri-iktal vejetatif semptomlar ile klinik çalışmalar sınırlı sayıdadır ve çoğu olgu düzeyinde bildirimlerdir. [8][9][10][11][12][13][14][15][16] Bu çalışmanın amacı, hasta çalışmamızda klinik nöbet semptomlarının sıklığını saptamak ve klasik lateralizan değeri yüksek bulgular yanında görece nadir görülen bulguların lateralizasyon değerini belirlemektir. İktal EEG'de iyi lateralize edilmiş TLE'li hasta çalışmasında iktal ve postiktal semiyoloji detaylı incelenmiştir.…”
Section: Introductionunclassified